Pengaruh Motivasi Terhadap Kinerja Guru di Sekolah Menengah Kejuruan - Windasari, Windasari (Universitas Negeri Semarang, 2020)
This study objective to analyze the impact of motivation on teachers performance Vocational High School in Bangil. Data collection techniques by distributed a questionnaire using a five-likert scale. The sampling technique used was cluster random sampling. Samples taken from each school amounted to 3 teachers from each department, so there were 42 respondents from 5 schools.. The analysis technique used to answer the research hypothesis uses simple linear regression. The results showed that teacher motivation had an effect on teacher performance in vocational high school